Psychosocial Well-Being, Mental Health, and Available Supports in an Arab Enclave: Exploring Outcomes for Foreign-Born and U.S.-Born Adolescents - Seff, Ilana; Gillespie, Alli; Bennouna, Cyril; Hassan, Wafa; Robinson, Mackenzie V.; Wessells, Michael; Allaf, Carine; Stark, Lindsay (Frontiers in Psychiatry, 2021)
Introduction: Few studies have assessed the impact of displacement, resettlement, and discrimination on well-being outcomes for adolescent refugees resettled within the U.S. Conducted in three charter schools in the intergenerational Arab enclave of the Detroit Metropolitan Area, this mixed-methods study assessed the mental health and psychosocial support for both U.S.- and foreign-born adolescents from the Middle East and North Africa region. Methods: A quantitative survey was used to collect data on 176 students. Key outcomes included hope, prosocial behaviors, resilience, depressive, anxiety, externalizing symptoms, stressful life events, perceived social support, and sense of school belonging. Differences in outcomes between U.S.- and foreign-born students were compared using T-tests. Regression analysis explored whether outcomes were gendered and correlated with years in the U.S. for foreign-born students. Qualitative data collection included key informant interviews with school staff and community service providers, student focus group discussions, and caregiver interviews. Interview transcripts were analyzed using thematic analysis and the constant comparative method. Results: No statistically significant differences between the foreign-born and U.S.-born groups were observed. However, analysis revealed that resilience decreased for male students with time spent in the U.S. Qualitative themes illuminated these results; shared cultural heritage allowed newcomer students to access relevant language and psychosocial support, while inter- and intra-group peer relationships strengthened students' dual language skills and identity formation. However, shifting gender expectations and role hierarchies for newcomer students revealed boys' increased stressors in the family domain and girls' better accessed support in the school context. Conclusion: The existence of an immigrant paradox in this enclave setting was not supported. Instead, findings highlight the reciprocal value of peer-based mentorships and friendships between U.S.- and foreign-born students with similar cultural backgrounds, the importance of social and emotional curricula and cultural competency training within schools, and the gendered effects of acculturation.